The Level Assessment of Extracellular Nucleic Acids in the Blood of Pregnant Women with Chronic Hypertension with Superimposed Preeclampsia - Omertayeva, Dinara; Muravlyova, Larissa; Ponomaryova, Olga; Molotov-Luchanskiy, Vilen; Bakirova, Ryszhan; Klyuev, Dmitriy; Mugazov, Miras (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Preeclampsia, chronic arterial hypertension is one of the causes of maternal and perinatal morbidity and mortality. AIM: The aim of our study was to assess the level of extracellular nucleic acids in red blood cells and blood plasma in pregnant women with severe preeclampsia, severe chronic hypertension, and pregnant women with chronic hypertension with superimposed preeclampsia. METHODS: A total of 107 pregnant women were examined who were hospitalized at the Regional Clinical Hospital and at the Regional Perinatal Center in Karaganda and 29 healthy non-pregnant women. Pregnant women were divided into four groups: 1 group – 32 pregnant with severe chronic hypertension, 2 group – 48 pregnant women with severe preeclampsia, 3 group – 35 women entered the group with chronic hypertension with superimposed preeclampsia, and group control – 29 healthy non-pregnant women of child bearing age (4th group – control). RESULTS: The content of ecNA in the erythrocytes of pregnant women with chronic hypertension with superimposed preeclampsia sharply increases relative to the control and comparison groups; in pregnant women with severe hypertension and severe preeclampsia, the level of ecNA is moderately higher relative to the control, but lower than in the main group. CONCLUSION: Our data indicate significant changes in the level of ecNA in pregnant women with various types of hypertension and require further research, but now, changes in the concentration of ecNA can be considered as one of the links in the pathogenesis of preeclampsia.